2004
DOI: 10.1210/me.2004-0211
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Nuclear Receptor Small Heterodimer Partner Represses Hepatocyte Nuclear Factor 3/Foxa Transactivation via Inhibition of Its DNA Binding

Abstract: Small heterodimer partner (SHP; NR0B2) is an atypical orphan nuclear receptor and acts as a coregulator of various nuclear receptors. Herein, we examined a novel cross talk between SHP and a forkhead transcription factor HNF3 (hepatocyte nuclear factor 3/Foxa. Transient transfection assay demonstrated that SHP inhibited the transcriptional activity of all three isoforms of HNF3, HNF3alpha, beta, and gamma. In vivo and in vitro protein interaction studies showed that SHP physically interacted with HNF3. Adenovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
96
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 62 publications
2
96
0
Order By: Relevance
“…Bile acid is an endogenous ligand of the farnesoid X receptor, which can profoundly activate SHP transcription (34), and SHP decreased the expression of CYP7A1 via the inhibition of LRH-1 activity (19,35). Additionally, bile acid-induced SHP can downregulate PEPCK and G6Pase expression by the repression of the transcriptional activity of HNF-4␣, FoxO1, and FoxA2 (23)(24). However, the correlation between SHP expression and type 2 diabetes, and/or antidiabetic agent, has not been previously elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bile acid is an endogenous ligand of the farnesoid X receptor, which can profoundly activate SHP transcription (34), and SHP decreased the expression of CYP7A1 via the inhibition of LRH-1 activity (19,35). Additionally, bile acid-induced SHP can downregulate PEPCK and G6Pase expression by the repression of the transcriptional activity of HNF-4␣, FoxO1, and FoxA2 (23)(24). However, the correlation between SHP expression and type 2 diabetes, and/or antidiabetic agent, has not been previously elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…SHP represses the transcriptional activity of a number of nuclear receptors (15)(16)(17)(18)(19)(20)(21)(22), as well as hepatocyte nuclear factor (HNF)-4␣ (NR2A1), FoxO1 (also known as FKHR) (23), and the forkhead transcription factor FoxA2 (also referred to as HNF-3␤) (24), which are the primary transcription factors that regulate PEPCK and/or G6Pase expression. Recent evidence suggests that SHP may perform a function in glucose homeostasis by the regulation of hepatic gluconeogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 In this study, we found that adenovirus-mediated overexpression of SHP successfully inhibited TGF-␤-stimulated PAI-1 and matrix protein expression in cultured kidney cell lines. Although the mechanism of repression by SHP is not clearly understood, previous reports have suggested that SHP represses transcription factor-mediated transactivation by inhibition of DNA binding, 22,38,39 recruitment of unknown corepressors, 40 -42 and interfering the interaction with coactivator p300. 25 In this study, we found that that SHP repressed Smad3 transactivation by inhibition of DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated the mechanisms by which SHP regulates target gene transcription without directly binding to target promoter sequences. SHP represses transcription factor-mediated transactivation by inhibiting DNA binding (Seol et al, 1996;Ourlin et al, 2003;Kim et al, 2004), by recruiting unknown corepressors (Johansson et al, 2000;Lee et al, 2000Lee et al, , 2002 and by interfering with the interaction with coactivator (Suh et al, 2006). Fiorucci et al (2004) showed that the inhibitory effect on AP-1 activity is mediated by a physical interaction between AP-1 and SHP that decreases AP-1 DNA binding.…”
Section: Discussionmentioning
confidence: 99%